Patient’s Decision to Disclose the Use of Traditional and Complementary Medicine to Medical Doctor: A Descriptive Phenomenology Study - Johny, Kelak; Whye, Lian Cheah; Razitasham, Safii (Hindawi Publishing, 2018)
Nondisclosure of traditional and complementary medicine (T&CM) use may cause individual to be at risk of undue harm. Tis study aimed to explore patient’s experience and views on their decision to disclose the use of T&CM to the doctor. An exploratory qualitative study using in-depth interview involving 10 primary care clinics attendees in Kuching was conducted. Te results indicated that disclosure of T&CM use will motivate them to get information, increase doctor’s awareness, and get support from family and friends for disclosure. Fear of negative relationship and negative response from doctors was a barrier for disclosure. Doctor’s interpersonal and communication skills of being involved, treating patients respectfully, listening attentively, respecting privacy, and taking time for the patient were a critical component for disclosure. Intrapersonal trust regarding doctor infuences their satisfaction on healthcare. Women are more open and receptive to a health concern and expressing negative emotions and tend to share problems, whereas men always described themselves as healthy, tended to keep their own personal feeling to themselves, and tended to not share. Te doctor should consider gender diferences in disclosure, their attitude towards T&CM use, and gained patient’s trust in the delivery of healthcare services. Good interpersonal and communication skills must be maintained between doctor and patients